1975
DOI: 10.1021/jm00242a006
|View full text |Cite
|
Sign up to set email alerts
|

Microbial models of mammalian metabolism. O-Dealkylation of 10,11-dimethoxyaporphine

Abstract: Microbial transformations of 10,11-dimethoxyaporphine were studied to determine the potential of microorganisms to produce monomethoxyaporphines. Ten microorganisms were identified as being capable of yielding apocodeine and/or isoapocodeine as the major metabolite in 24 and 20% yield, respectively. Cunninghamella blakesleeana (ATCC 9245) converted 10,11-dimethoxyaporphine quantitatively into isapocodeine. O-Dealkylation of this aporphine system is a facile microbial transformation, and the 10-methoxyl group i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…Our findings with C. blakesleeana and C. echinulata (115), which produced mostly isoapocodeine, support the result of Boothroyd et al (113) that selective 0-dealkylation may be achieved with different microorganisms.…”
Section: Scheme Zvsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings with C. blakesleeana and C. echinulata (115), which produced mostly isoapocodeine, support the result of Boothroyd et al (113) that selective 0-dealkylation may be achieved with different microorganisms.…”
Section: Scheme Zvsupporting
confidence: 90%
“…We have conducted several experiments on microbial 0-dealkylations, predominantly with methoxylated aporphine and benzylisoquinoline derivatives (115). Cannon et al (116) studied the synthesis of the isomeric monomethyl metabolites of apomorphine and metabolism of apomorphine in a catechol-0-methyltransferase liver preparation.…”
Section: Scheme Zvmentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques and different approaches used in microbial transformations have been mentioned and reviewed by several authors [1,4,11,[13][14][15][16][17]. The compounds can be metabolized by using either different pure enzymes or simply cultivated microbial whole cells [18][19][20][21][22].…”
Section: Development Of Microbial Modelsmentioning
confidence: 99%
“…elegans (ATCC 9245) was selected for this study, because it has been reported that it had a faculty for the O-demethylation of 10, II-dimethoxyaporphine. 10) The fungus was grown with shizandrin in Erlenmeyer's flaks for 15 days. The analysis of the culture broth by high pressure liquid chromatography (HPLC) suggested the existence of four main metabolites (Fig.…”
Section: V----ivmentioning
confidence: 99%